2021
DOI: 10.2174/1381612826666201118092422
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neuroinflammatory Potential of Polyphenols by Inhibiting NF-κB to Halt Alzheimer's Disease

Abstract: : Alzheimer's disease (AD) is an irrevocable chronic brain disorder featured by neuronal loss, microglial accumulation, and progressive cognitive impairment. The proper pathophysiology of this life-threatening disorder is not completely understood and no exact remedies are found yet. Over the last few decades, research on AD has mainly highlighted in pathomechanisms linked to a couple of the major pathological hallmarks, including extracellular senile plaques, made of amyloid-β (Aβ) peptides, and intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 173 publications
0
17
0
Order By: Relevance
“…[ 144 , 145 ]. Its activation has been associated with A β -initiated neurotoxicity [ 146 ], and it has been found in the brains of Alzheimer's patients [ 147 ]. Natural substances can hinder AD neurodegeneration with fewer adverse effects than synthetic medications.…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%
“…[ 144 , 145 ]. Its activation has been associated with A β -initiated neurotoxicity [ 146 ], and it has been found in the brains of Alzheimer's patients [ 147 ]. Natural substances can hinder AD neurodegeneration with fewer adverse effects than synthetic medications.…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%
“…Increased activation of proinflammatory signaling cascades recruited by the ISR has also been demonstrated to be increased in AD (Colangelo et al 2002). Positive feedback of this proinflammatory loop has been proposed to induce chronic neuroinflammation and contribute to neurodegenerative consequences in AD (Jones and Kounatidis 2017;Ju Hwang et al 2019;Lindsay et al 2021;Uddin et al 2021). For example, induction of miRNAs by NF-κB in AD directly results in the downregulation of previously discussed SYN2 (Lukiw 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In pheochromocytom PC12 cells, OA improved catalase and SOD activities, attenuated release of IL-6 and TNF-α and decreased malondialdehyde formation [231]. When OA extracts from Aralia cordata were added to cultured rat cortical neurons, it inhibited neuronal death, glutamate release, and generation of ROS induced by Aβ-peptide (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [232]. In mouse models, OA administration improved memory loss, alleviated neuronal damage and synapse changes in Aβ25-35-induced AD mouse models [233].…”
Section: Oleanolic Acidmentioning
confidence: 99%
“…However, an abnormal phosphorylation of Akt substrates was observed in AD brain implying that therapeutics directed to activate the Akt pathway requires prudence in neurodegenerative diseases [26]. On the other hand, models of AD [27] and T2DM [28] showed significant improvements following downregulation of inflammatory responses. Recent data revealed that small bioactive compounds exhibit potential protective functions and may be considered as alternative resource for pharmaceutical drug design against insulin resistance-related disease, providing new direction in drug discovery.…”
Section: Figurementioning
confidence: 99%